Patient safety culture in central sterile supply departments: nurses' perceptions - Sara Satie Yamamoto; Gisela Maria Schebella Souto de Moura; Diovane Ghignatti da Costa; Ana Maria Müller de Magalhães; Jeane Aparecida Gonzales Bronzatti (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To know the perceptions of nurses with experience in Central Sterile Supply Departments about the safety culture. Methods A qualitative study developed with 12 nurses from hospitals in the South and Southeast Brazilian regions, with data collected in March 2021 through online interviews. Bardin's content analysis was performed with the support of the IRaMuTeQ software. Results The interpretations were classified considering the following aspects: indirect care provided by Central Sterile Supply Departments (27.16%), low visibility of Central Sterile Supply Departments for patient safety (26.92%), difficulty in internal communication (30.69%) and difficulties learning from errors and fair culture (15.23%). Conclusions The perceptions about the safety culture are related to the quality control of processes and to infection prevention; however, there were perceptions about its low recognition and devaluation. The communication, learning from errors and fair culture subcultures proved to be weak.